Context and Progress of Domestic and International Low-Altitude Economic Research Based on the CiteSpace Software - Liao Wang; Cao Xiaoshu; Yuan Liyang; Zhong Zhiping (Redai dili)
As an important economic form for the innovation and development of human society, since the 21st century, the low-altitude economy has become one of the key ways to promote China's modern industrial development, with its unique charm and broad application prospects. Research on the low-altitude economy of manned vehicles has a long history. However, this research is still growing; and there are many ambiguities within the human-cultural research of low-altitude economies. Therefore, it is necessary to review the existing results so as to promote the development of a theoretical and methodological system for low-altitude economic research. Based on data from the Web of Science (WOS), Scoups, and CNKI databases with the low-altitude economy as the research theme, the CiteSpace software was used to comprehensively sort out the publication status, research content, and research lineage of domestic and foreign low-altitude economy research. This study analyzes and summarizes the characteristics of the publication, subject matter, and characteristics and trends of the various phases. The results show that: (1) Although the leading figures and research teams of domestic and foreign low-altitude economy research have initially appeared, there are fewer cross-institutional academic contacts and a broad academic consensus is yet to be formed. (2) There are also differences in the development history and research characteristics of domestic and foreign low-altitude economy research, but in the early stage of the research, the focus is mainly on general aviation. It then moves to a new era of drone dominance that is centered on the low-altitude economy after 2010. (3) As is, foreign studies have focused on, for example, the exploration of UAV models and their engineering technology, UAV traffic management systems, UAV application scenarios. On the contrary, Chinese studies focus on the reflection and summary of the reform of low-altitude airspace, construction of UAV systems and their industrial development, etc. (4) The directional shift of the low-altitude economy from the natural space to the human-cultural space is an important feature in this growth period but the current low-altitude economy research on human culture is still in the trial phase. Therefore, it is recommended that scholars establish a scientific system suitable for the development of low-altitude economies in China, expand research perspectives and interdisciplinary cooperation, and strengthen extensive communication and exchanges among scholars, which helps construct a diversified inter-institutional, interdisciplinary, and inter-geographical cooperation network. In addition, it will deeply excavate the human-earth relations and spatial organization concepts in the study of low-altitude economies and integrate natural-social-economic-humanities perspectives on intelligent, synergistic, and sustainable development of UAVs, as well as systematically expose the UAV industry chain, UAV-related supporting facilities, market consumption, and public attitudes. This study aims to accelerate the high-quality development of China's low-altitude economy and comprehensively promote its modern development.